The level of integration of various models for organisational change management in Slovenian organisations. (16th October 2008) - Bukovec, Boris; Markic, Mirko
The aim of this article is to ascertain the extent to which the contemporary approaches and models such as the ISO Standard 9001, the EFQM Model of Excellence, 20 Keys, BSC, Six Sigma and BPR are used in organisational systems for the continuous improvement of business success. Quantitative research was carried out in order to ascertain how widespread the use of these approaches is in the Republic of Slovenia. Our conclusion is that the extent to which various models for change management are used is strongly influenced by the degree to which managers are familiar with them, and is co-dependent on the life cycle of each respective company.